2009
DOI: 10.1098/rspb.2009.0214
|View full text |Cite
|
Sign up to set email alerts
|

Llandovery sporomorphs and graptolites from the Manbo Formation, the Mojiang County, Yunnan, China

Abstract: Llandovery sporomorphs and graptolites have been recovered from the Manbo Formation, Mojiang area, western Yunnan, China, which belonged to the Indo-China Palaeoplate in the Palaeozoic. The graptolite fauna, including 8 genera and 12 species, is considered Mid Telychian, Llandovery in geological age, confirming the existence of Llandovery rocks in this region. The Silurian stratigraphical sequence of this area is reconsidered as in the ascending order: Manbo Formation (Llandovery-early Wenlock), Shuiqing Forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This view was reiterated by Zhang et al (2014, p. 28). However, as Wang and Zhang (2010) acknowledged, Silurian cryptospore species are cosmopolitanevery one of the seven species recorded by Wang and Zhang (2010) has a very wide distribution, from high southern palaeolatitudes (sites in North Africa and Argentina) through to localities on Laurentia and South China widely accepted to have been at tropical palaeolatitudes. On the basis that it is thought that spores could not be distributed across wide oceans, Steemans and Pereira (2002) concluded that the uniformity of Upper Ordovician and Llandovery sporomorph assemblages could be best explained using palaeogeographical reconstructions with only narrow oceans separating the continents.…”
Section: Sporomorphs From Yunnan (Indochina)mentioning
confidence: 99%
See 1 more Smart Citation
“…This view was reiterated by Zhang et al (2014, p. 28). However, as Wang and Zhang (2010) acknowledged, Silurian cryptospore species are cosmopolitanevery one of the seven species recorded by Wang and Zhang (2010) has a very wide distribution, from high southern palaeolatitudes (sites in North Africa and Argentina) through to localities on Laurentia and South China widely accepted to have been at tropical palaeolatitudes. On the basis that it is thought that spores could not be distributed across wide oceans, Steemans and Pereira (2002) concluded that the uniformity of Upper Ordovician and Llandovery sporomorph assemblages could be best explained using palaeogeographical reconstructions with only narrow oceans separating the continents.…”
Section: Sporomorphs From Yunnan (Indochina)mentioning
confidence: 99%
“…Telychian (upper Llandovery) graptolites from Mojiang County were initially illustrated and discussed briefly by Wang and Zhang (2010), then described in detail (with some different identifications from those in Wang and Zhang, 2010) by Zhang et al (2013), with a few species re-illustrated by Zhang et al (2014, fig. 3.12).…”
Section: Graptolites From Yunnan (Indochina)mentioning
confidence: 99%
“…(Geikie, 1908) The foregoing citations by eminent geologists of the day show without doubt the esteem in which these female geologists were held in for their pioneering work in Wales. Indeed some of their research, such as Wood (1901-1918) and Ida Slater (1907) is still widely cited (Leme et al, 2008;Storch and Loydell, 1996;Wang and Zhang, 2010) and is the authoritative work today.…”
Section: Gertrude Elles 1919 (Murchison Medal)mentioning
confidence: 97%
“…Palaeobiogeography is a topic of general interest to palaeontologists and a thread through several publications of this special issue: Zhou et al (2010b) present a nice analysis on the evolutionary trends and palaeobiogeography of an Ordovician trilobite genus. Wang & Zhang (2010a) provide new information concerning the Silurian biostratigraphy and palaeogeography based on new data from sporomorph and graptolite fossils. Sha's (2010) work on non-marine Cretaceous trigonioidid bivalves provides new information concerning the palaeogeography in the Cretaceous of Asia.…”
mentioning
confidence: 99%
“…Wang & Zhang (2010a) provide new information concerning the Silurian biostratigraphy and palaeogeography based on new data from sporomorph and graptolite fossils. Sha's (2010) work on non-marine Cretaceous trigonioidid bivalves provides new information concerning the palaeogeography in the Cretaceous of Asia.…”
mentioning
confidence: 99%